Physicochemical characteristics, GABA content, antimicrobial and antioxidant capacities of yogurt from Murrah buffalo milk with different fat contents - Mohsin, Aliah Zannierah; Marzlan, Anis Asyila; Muhialdin, Belal J.; Wai, Lew Kah; Mohammed, Nameer Khairullah; Meor Hussin, Anis Shobirin (Elsevier, 2022)
This study aimed to prepare yogurt from Murrah buffalo milk with high GABA content and low fat content while keeping the physicochemical characteristics, antimicrobial effects, and antioxidant capacity within acceptable levels. Yogurt samples were prepared using buffalo milk by adjusting the fat content to 0.2%, 3.5%, and 6.5%. The results showed that the fat content had no significant effects on the pH, titratable acidity, water activity, and cell viability. However, the fat content significantly affected the viscosity, particle size, and texture profile analysis of the yogurt. The GABA content was significantly higher in the 0.2% fat yogurt (61.57 ± 3.22 mmol L−1) compared to the 3.5% fat yogurt (43.64 ± 1.99 mmol L-1) and 6.5% fat yogurt (27.84 ± 2.64 mmol L−1). Glutamic acid and proline were the most abundant amino acids in the yogurt. In contrast, saturated fatty acids (butyric, lauric, myristic, palmitic, stearic, and oleic) and linoleic acid were abundant. Yogurt with 3.5% fat showed significantly high antioxidant capacity and antimicrobial effects on E. coli O157 and Salmonella sp. Based on the results, fat content significantly affects the rheological properties, GABA content, and antioxidant and antimicrobial capacities of yogurt. In the future, 3.5% fat should be chosen as the optimized formula for large-scale yogurt production from Murrah buffalo milk.